2015 IEEE UP Section Conference on Electrical Computer and Electronics (UPCON) 2015
DOI: 10.1109/upcon.2015.7456741
|View full text |Cite
|
Sign up to set email alerts
|

Detection of optic disc and cup from color retinal images for automated diagnosis of glaucoma

Abstract: Glaucoma is the major cause of ocular damage and vision loss in which increased Intraocular Pressure (IOP) of the eye progressively damages the optic nerve. In this proposed study, an automatic system is developed for glaucoma detection by extracting various features like vertical Cup to Disc Ratio (CDR), Horizontal to Vertical CDR (H-V CDR), Cup to Disc Area Ratio(CDAR), and Rim to Disc Area Ratio (RDAR) from digital fundus images through segmentation of Optic Disc (OD), cup and neuroretinal rim. OD is segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…Table III and Table IV discussed performance of the proposed GlaucoNet+ model with different classification setups (Table III) and configuration (Table IV); however to further examine efficacy of our proposed model in comparison to the other existing glaucoma detection and classification methods, we have performed analysis based on secondary resources (reviewing existing methods or allied papers). [49] 84.38 --- [54] 95.50 --- [60] --- [64] 88.00 --- [35] --98.60 - [36] 99.20 -86.00 - [65] ---- [47] 80.00 -95.00 - [48] 97.00 --- [57] 98 --- [39] 94.10 -91.80 - [75] 90.00 --- [40] --92.00 - [33] 100.00 -94.00 - [59] ---- [66] 89.6 (NB) 97.6(AN N) --- [67] 92.00 --- [68] ---- [69] 72.38 --- [70] 79.00 -87.00 - [71] 83.10 --- [62] 93.00 --- [72] 96.67 -100.00 - [73] 91.00 --- [74] 92.00 --- [4] 0.8478 - [55] 88. Observing the results, it can be found that the proposed GlaucoNet+ model with Hybrid feature extraction and SVM (polynomial) with 10-fold cross validation outperforms major existing approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Table III and Table IV discussed performance of the proposed GlaucoNet+ model with different classification setups (Table III) and configuration (Table IV); however to further examine efficacy of our proposed model in comparison to the other existing glaucoma detection and classification methods, we have performed analysis based on secondary resources (reviewing existing methods or allied papers). [49] 84.38 --- [54] 95.50 --- [60] --- [64] 88.00 --- [35] --98.60 - [36] 99.20 -86.00 - [65] ---- [47] 80.00 -95.00 - [48] 97.00 --- [57] 98 --- [39] 94.10 -91.80 - [75] 90.00 --- [40] --92.00 - [33] 100.00 -94.00 - [59] ---- [66] 89.6 (NB) 97.6(AN N) --- [67] 92.00 --- [68] ---- [69] 72.38 --- [70] 79.00 -87.00 - [71] 83.10 --- [62] 93.00 --- [72] 96.67 -100.00 - [73] 91.00 --- [74] 92.00 --- [4] 0.8478 - [55] 88. Observing the results, it can be found that the proposed GlaucoNet+ model with Hybrid feature extraction and SVM (polynomial) with 10-fold cross validation outperforms major existing approaches.…”
Section: Resultsmentioning
confidence: 99%
“…A ideia básica é começar com uma curva inicial e depois deformar essa curva para o limite do objeto que se deseja segmentar. Essa deformação ocorre sob algumas restrições da imagem (Lotankar et al;2015). Joshi et al (2011) propuseram um método para a segmentação do disco óptico e da escavação que se baseia em um modelo de contorno ativo e em evidências anatômicas, tais como curvas de vasos.…”
Section: Contorno Ativounclassified
“…The detection of optic disc and optic cup from colour retinal images for glaucoma detection is approached in [4]. An automatic system is developed for glaucoma detection by extracting various features like vertical CDR, Horizontal to Vertical CDR (H-V CDR), CDAR and Rim to Disc Area Ratio from digital fundus images through segmentation of Optic disc, cup and neuro retinal rim.…”
Section: Introductionmentioning
confidence: 99%